Serum- and Glucocorticoid-Inducible Kinase 1 (SGK1) Increases Neurite Formation through Microtubule Depolymerization by SGK1 and by SGK1 Phosphorylation of tau - Yang, Ying C. (American Society for Microbiology, 2006)
Serum- and glucocorticoid-inducible kinase 1 (SGK1) is a member of the Ser/Thr protein kinase family that regulates a variety of cell functions. Recently, SGK1 was shown to increase dendritic growth but the mechanism underlying the increase is unknown. Here we demonstrated that SGK1 increased the neurite formation of cultured hippocampal neurons through microtubule (MT) depolymerization via two distinct mechanisms. First, SGK1 directly depolymerized MTs. In vitro MT depolymerization experiments revealed that SGK1, especially N-truncated SGK1, directly disassembled self-polymerized MTs and taxol-stabilized MTs in a dose-dependent and ATP-independent manner. The transfection of sgk1 to HeLa cells also inhibited MT assembly in vivo. Second, SGK1 indirectly depolymerized MTs through the phosphorylation of tau at Ser214. An in vitro kinase assay revealed that active SGK1 phosphorylated tau Ser214 specifically. In vivo transfection of sgk1 also phosphorylated tau Ser214 in HEK293T cells and hippocampal neurons. Further, sgk1 transfection significantly increased the number of primary neurites and shortened the length of the total process in cultured hippocampal neurons. These effects were antagonized by the cotransfection of the tauS214A mutant plasmid. Dexamethasone, a synthetic glucocorticoid, mimics the effect of sgk1 overexpression. Together, these results suggest that SGK1 enhances neurite formation through MT depolymerization by a direct action of SGK1 and by the SGK1 phosphorylation of tau.